Are ACE inhibitors and ARBs more beneficial than harmful in the treatment of severe COVID-19 disease? - Christian A Devaux (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2020)
After starting in China four months ago, the COVID-19 pandemic now affects most countries and has already caused more than 200,000 deaths by April 26, 2020 Under chest computerized tomography scans, the majority of severe COVID-19 patients show bilateral ground glass-like opacities and subsegmental areas of consolidation indicative of pneumonia. If in its severe forms this disease affects the lungs, in many cases it is also responsible for a multi-organ failure with adverse myocardial remodeling, myocardial stress, and cardiomyopathy [1,2].